Studi Pengaruh Penambahan Hidrogen Peroksida (H2O2) Terhadap Degradasi Methylene Blue Menggunakan Fotokatalis TiO2 – Bentonit - Wardhani, Sri; Purwonugroho, Danar; Suhernadi, Arif (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Photocatalyst is a material that is able to accelerate the reaction rate of oxidation or reduction through a photochemical reaction. The aims of this study was examine the influence of addition of H2O2 and duration of irradition against photodegradation of methylene blue using TiO2-bentonite. Photodegradation was carried out with 10 mg/L at 25 mL of methylene blue and 50 mg of photocatalyst with variation of H2O2 addition of 0,1; 0,2; 0,3; 0.4; 0,5 dan 0,75 mL and variations of irradition duration of 20, 30, 40, 50 and 60 minute. The result showed that the highest fotodegradation of methylene blue occured in the addition of 0,2 mL of H2O2 and irradition duration of 60 minute with 93,93 % of degradation percentage. Keywords             : bentonite, TiO2, methylene blue, hydrogen peroxyde (H2O2), photodegradation.